Quantification of Viable Brochothrix thermosphacta in Cold-Smoked Salmon Using PMA/PMAxx-qPCR - Bouju-Albert, Agnès; Saltaji, Sabrina; Dousset, Xavier; Prévost, Hervé; Jaffrès, Emmanuel (Frontiers in Microbiology, 2021)
The aim of this study was to develop a rapid and accurate PMA-qPCR method to quantify viable Brochothrix thermosphacta in cold-smoked salmon. B. thermosphacta is one of the main food spoilage bacteria. Among seafood products, cold-smoked salmon is particularly impacted by B. thermosphacta spoilage. Specific and sensitive tools that detect and quantify this bacterium in food products are very useful. The culture method commonly used to quantify B. thermosphacta is time-consuming and can underestimate cells in a viable but not immediately culturable state. We designed a new PCR primer set from the single-copy rpoC gene. QPCR efficiency and specificity were compared with two other published primer sets targeting the rpoC and rpoB genes. The viability dyes PMA or PMAxx were combined with qPCR and compared with these primer sets on viable and dead B. thermosphacta cells in BHI broth and smoked salmon tissue homogenate (SSTH). The three primer sets displayed similar specificity and efficiency. The efficiency of new designed rpoC qPCR on viable B. thermosphacta cells in SSTH was 103.50%, with a linear determination coefficient (r2) of 0.998 and a limit of detection of 4.04 log CFU/g. Using the three primer sets on viable cells, no significant difference was observed between cells treated or untreated with PMA or PMAxx. When dead cells were used, both viability dyes suppressed DNA amplification. Nevertheless, our results did not highlight any difference between PMAxx and PMA in their efficiency to discriminate viable from unviable B. thermosphacta cells in cold-smoked salmon. Thus, this study presents a rapid, specific and efficient rpoC-PMA-qPCR method validated in cold-smoked salmon to quantify viable B. thermosphacta in foods.